PBG 3. Characterization , evaluation, seed reproducibility and cluster analysis of open-pollinated salad tomato accessions in La Trinidad, Benguet (2018)
Eight promising open-pollinated accession of salad tomatoes such as 35-1, 20-05, 396-27, 886-76,39-1,40-N,46-N and 42-N were characterized and evaluated based on growth, yield and seed reproducibility under La Trinidad, Benguet condition. The cluster analysis based on fresh fruit and seed yield was also determined. The varieties differed in various characters considered except for percent plant survival, length of internode, maturity, fruit set, seed yield per plant and weight and number of seed per fruit. Accession 42-N significantly produced in the tallest plant with 30.88cm but comparable with the height of Accession 396-27, 40-N, 39-1, 46-N and 886-76. accessions 42-N , 39-1 and 886-76 were the earliest to flower at 36 DAT. Accessions 35-1, 42-N, 396-27, 40-N and 46-N produced 7 to 8 flowers per cluster. Accession 886-76 and 20-05 produced the significantly highest number of cluster (18) per plant. Accession 886-76 recorded the highest fresh fruit yield among the test materials evaluated. In terms of seed reproducibility, the eight open-pollinated salad tomato varieties evaluated did not differ significantly. The seed yield per plant ranged from 3.4g (20-05) to 7.7g(Accessions 886-76 and 39-1). The number of seeds per fruit ranged from 141 to 188. Accession 46-N produced the numerically highest number of seed per fruit and weight of seed per fruit, 1000-seed weight and percent germination. The eight open-pollinated accessions of salad tomato formed four distinct clusters at 1% of dissimilarity coefficient based on fresh fruit and seed yield. This indicated that each cluster of the open-pollinated accessions possesses distinct characters that could be used in choosing varieties for fresh fruit and seed production. Accession 35-1 and 42-N comprised the first cluster, cluster two is composed of Accessions 40-N, 20-05 and 886-76. Accessions 396-27 and 39-1 comprised the 3rd cluster and cluster 4 is composed of Accession 46-N.